Photography, temporality, and modernity - Belden-Adams, Kris, author.
1 online resource.
Keywords: This book examines the photography's unique capacity to represent time with a degree of elasticity and abstraction. Part object-study, part cultural/philosophical history, it examines the medium's ability to capture and sometimes "defy" time, while also traveling as objects across time-and-space nexuses. The book features studies of understudied, widespread, practices: studio portraiture, motion studies, panoramas, racing photo finishes, composite college class pictures, planetary photography, digital montages, and extended-exposure images. A closer look at these images and their unique cultural/historical contexts reveals photography to be a unique medium for expressing changing perceptions of time, and the anxiety its passage provokes.